Pengaruh Penerapan Media Quiziz dalam Meningkatkan Minat dan Hasil Belajar Peserta Didik pada Mata Pelajaran Fisika Kelas X IPA - Musdar Musdar (Journal on Education, 2023)
The research aims to determine the effect of applying Quizizz media as a learning medium on increasing students' interest and learning outcomes. The type of research used in this study was a quasi-experimental design with nonequivalent control group design. The sampling technique used was saturated sampling with a total of 42 respondents in each of the experimental and control groups, the instruments used were questionnaires and tests in the form of multiple choices. Data were analyzed using descriptive and inferential statistical tests, namely through the t-test with values ​​obtained t-count = 7.026 with a value of t-table = 2.021 so that it can be concluded that the value of t-count ˃ t-table is 7.026 ˃ 2.021 or it can be said that H-0 is rejected and H-a is accepted in learning interest while in learning outcomes obtained value t-count = 3.055 and t-table = 2.021 so that it can be concluded that the value of t-count ˃ t-table is 3.055 ˃ 2.021 or it can be said that H-0 is rejected and H-a is accepted. Based on the average score, it shows that there is an influence on the use of Quizizz media as a learning medium which is shown in changes in student behavior after the media is applied, such as starting to actively ask questions during the learning process, doing assignments given by the teacher, and not getting sleepy during learning activities. so based on this the use of Quizizz media as a learning medium is appropriate to use in increasing interest which can then improve student learning outcomes.